Analysis of factors associated with postoperative systemic inflammatory response syndrome in patients with urine culture-positive stone lithotripsy - Li, Xinwei; Zhang, Yuanpeng; Ruan, Hailong; Zhang, Xiaoping; Liu, Lei (Frontiers in Surgery, 2024)
IntroductionSystemic inflammatory response syndrome (SIRS) is a significant postoperative complication following lithotripsy, particularly in patients with positive urine cultures. Understanding the factors that contribute to the development of SIRS in these patients is crucial for improving clinical outcomes and reducing morbidity.Materials and methodsFrom 2022 to 2023, patients with preoperative positive urine culture who underwent minimally invasive uroscopic lithotripsy in Wuhan Union Hospital were retrospectively analyzed.ResultsA total of 393 patients with positive urine cultures underwent endoscopic lithotripsy, and 13.2% (52/393) were diagnosed with SIRS by relevant indicators after surgery. Multivariate logistic regression was used to study the risk factors for the occurrence of SIRS in patients postoperatively, which were preoperative positive WBC in urinalysis (OR = 5.685, p = 0.0051) and postoperative hemoglobin drop of greater than 5 g/L (OR = 2.180, p = 0.0145). Notably, preoperative upper urinary tract drainage was found to be a protective factor (OR = 0.4029, p = 0.0302), and postoperative C-reactive protein (CRP) value (OR = 1.025, p < 0.0001) and procalcitonin (PCT) value (OR = 1.066, p < 0.0001) were predictive factors. Besides, postoperative hemoglobin drop showed a weak correlation with surgical duration (r = 0.1589, p = 0.0016).ConclusionsIn summary, our study identifies key factors affecting the occurrence of SIRS after lithotripsy for urine culture-positive stone: preoperative positive WBC in urinalysis, postoperative hemoglobin drop, and preoperative upper urinary tract drainage. And monitoring postoperative CRP and PCT levels helps to predict SIRS.